Reflexões manicomiais – resíduos poéticos de um profissional do Ipq / Manicomial reflexions – poetic residues of a Professional of IPq - Alegre, Ledemir (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2013)
A colônia psiquiátrica Santana foi construída em 1941, com 300 leitos. Nos anos de 1960 chegou a ter 2000 internos. Depois foi denominada Hospital e Colônia Santana. A lógica da reforma psiquiátrica mexeu profundamente com a rotina do Hospital que foi jogado no impasse de modernizar-se ou sucumbir. Nos anos de 1990 ficou com um contingente de rejeitados e decidiu guardá-los. A Port. 52 de 20 de janeiro de 2004 do Ministério da Saúde estabeleceu novos padrões para os hospitais psiquiátricos e a Colônia teve que se repensar. O Instituo de Psiquiatria, nome atual, vive o drama do fantasma do passado com seus pacientes-moradores e a incerteza da modernidade. E o futuro pede respostas. ABSTRACT: The Psychiatric Colony Santana was built in 1941, with 300 beds. In the 1960´s grew to 2000 patients. Later it was named Santana Hospital and Colony. The logic of the psychiatric reform deeply interfered with the routine of the hospital that faced the challenge of modernize or perish. In the 1990s the hospital was left with a contingent of rejected patients and decided to keep them in the regime of asylum. In 2004 the Ministry of Health established new standards for psychiatric hospitals and the colony had to rethink itself. The Institute of Psychiatry, its current name, now faces the the ghost of its past embodied in their patients-residents and bringing the uncertainty of modernity. And the future calls for answers. Keywords: Psychiatry. Psychiatric reform. Asylum. Deinstitutionalization. Colônia Santana.